Aplicación de bioestimulantes para reducir la caída de hojas en Yerba Mate (Ilexparaguariensis) (Journal on studies and research of academic knowledge, 2014)
Loss of leaves in plantations of Illex Paraguariensis, phenomenom of great economic impact attributed to several factors. Among them, we can mention as most  important causes, the senescense atributed to genetic factors of the plant or population, root or foliar diseases low fertility, excessive exposition tos hade and the effect of weather factors such as frost, drough and abundant rainfall. The objective of this research was to reduce the amount of falling leaves during the productive season by aplication of bio-stimulants or combinations of itIt was used a design of randomized blocks of repetitions, 7 treatments and 6 plants per pot. During th 2013-2014 campaign were collected and weighed fallen leaves per plot and harvested the plots by the end of the campaign. The results were analized by variance (0.05) with no statistical difference between the bio-stimulants assessed.
Keywords: Loss of leaves; bio stimulant; hormones